Analisa Dampak Covid-19 terhadap Kinerja Keuangan Perusahaan Pembiayaan di Indonesia - Maria Esomar (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
The financing industry in Indonesia faces significant challenges due to the Covid-19 pandemic. The amount of financing channeled to the public and debtors’ ability to pay decreases. The purpose of this study is to analyze the impact of Covid-19 on the financial performance of finance companies by analyzing financial ratios, namely the Financing to Deposit Ratio (FDR), NPF (NonPerforming Financing (NPF) Return on Assets (ROA) and Return on Equity (ROE). This study applies a quantitative approach because the data collected are numbers. The data used are secondary data in the form of finance company statistics published by the Financial Services Authority (OJK), within the period of 9 months before (June 2019 - February 2020) and 9 months after (April 2020 - December 2020) the announcement of the first Covid-19 case in Indonesia on March 2nd, 2020. The test is conducted using th Paired Sample T-Test. The results of the data processing display that there are differences in the financial performance of finance companies in Indonesia before and after the Covid-19 which can be seen from the results of the Table of Paired Sample T-Test for the ratio of FDR, NPF, ROA, and ROE. Keywords : Financial performance, FDR, NPF, ROA, ROE